Thermal Maturity Map Based on Vitrinite Reflectance of Yamama Formation in Basrah Oil Fields, South of Iraq - Handhal, Amna M.; Al-Abadi, Alaa M. (Journal of Petroleum Research and Studies, 2024)
This study aims to create a detailed thermal maturity map based on vitrinite reflectance in the Basrah oil fields in southern Iraq. The specific objective was to determine areas with the highest thermal maturity within the Yamama Formation. The selected fields for analysis were WQ-60, Lu-12, Zb-42, Nr-12, Mj-12, and Ru-72, which belong to the West Qurna, Luhas, Zubair, Nahr Umar, Majnoon, and Rumaila oilfields, respectively. The Petromod 1D software was used for basin modeling and thermal history reconstruction. By inputting geological and geophysical data, the software enabled the construction of a comprehensive thermal basin history. The primary focus was on evaluating vitrinite reflectance values, which serve as a proxy for thermal maturity. The results of the study revealed significant variations in thermal maturity within the Yamama Formation across the selected fields. The Nahr Umar field (Nr-12) exhibited the highest thermal maturity, characterized by elevated vitrinite reflectance values. This indicates that organic matter within the Yamama Formation has undergone significant heating and maturation processes in this particular field. On the other hand, the Zubair field (Zb-12) displayed the lowest vitrinite reflectance values, suggesting a lower level of thermal maturity. This could be attributed to different burial histories, variations in the thermal gradient, or other tectonic movements in the area.